2007
DOI: 10.1080/00952990701301319
|View full text |Cite
|
Sign up to set email alerts
|

A Perfect Platform: Combining Contingency Management with Medications for Drug Abuse

Abstract: Contingency management (CM) procedures, which provide concrete reinforcers or rewards contingent on verification of discrete targeted behaviors, such as drug-free urines, have been demonstrated to be effective in a number of clinical trials. However, to date there have been only a few that have capitalized on the unique strengths and capabilities of CM as an ideal platform to improve response to or address weaknesses of many pharmacotherapies used in the treatment of drug abuse. In this review, we describe the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 121 publications
0
26
0
Order By: Relevance
“…It is only natural that any profession should continue to evolve and develop its primary focus or product, and in this manner, the field of addiction treatment is no different from any other. However, because of the various factors that influence addiction treatment, primarily motivated by legislation, ongoing research, spending, and outcomes, updates in addiction treatment technology have occurred regularly but have not been widely disseminated and adopted in the field (Carroll & Rounsaville, 2007;Hoge et al, 2002). Moreover, changes in treatment interventions often reflect our expanding knowledge of addiction.…”
Section: Increasingly Complex Interventionsmentioning
confidence: 97%
“…It is only natural that any profession should continue to evolve and develop its primary focus or product, and in this manner, the field of addiction treatment is no different from any other. However, because of the various factors that influence addiction treatment, primarily motivated by legislation, ongoing research, spending, and outcomes, updates in addiction treatment technology have occurred regularly but have not been widely disseminated and adopted in the field (Carroll & Rounsaville, 2007;Hoge et al, 2002). Moreover, changes in treatment interventions often reflect our expanding knowledge of addiction.…”
Section: Increasingly Complex Interventionsmentioning
confidence: 97%
“…CM interventions targeting substance abuse, for example, use technology-based methods to detect drug metabolites and research assistants or counselors to deliver monetary consequences based on evidence of abstinence (for a review, see Silverman 2004). In addition to targeting substance use, technology can be used with CM interventions to promote medication adherence (Carroll and Rounsaville 2007). Several randomized clinical trials have demonstrated that CM can promote adherence to HAART based on MEMS cap openings in HIV-infected drug users (Rigsby et al 2000; Rosen et al 2007; Sorensen et al 2007).…”
Section: Technology-based Interventions To Promote Healthmentioning
confidence: 99%
“…Cash rewards are provided to study participants for (a) cannabis abstinence, and (b) visit attendance (i.e., attending scheduled study visits). This CM intervention is based on prior use of CM in the treatment of cannabis use disorders previously reported in the literature [9, 15, 5962]. This “two-tiered” CM approach was used with significant effect on both study retention and cannabis abstinence in a prior young adult CM study [59].…”
Section: 0 Study Design and Proceduresmentioning
confidence: 99%
“…A recent meta-analysis showed modest benefit with behavioral treatments targeting CUDs (i.e., contingency management, relapse prevention, motivational interviewing, cognitive behavioral therapy, and combinations) compared to control conditions [6], yet there remains substantial room for improvement, as the majority of patients fail to achieve sustained periods of abstinence [79]. The development of pharmacological interventions to complement behavioral treatments represents a potential avenue to improve outcomes [1014], and contingency management (CM) has specifically been identified as a preferred evidence-based behavioral platform to conduct pharmacotherapeutic efficacy trials [15]. Several promising agents to treat CUDs exist [16, 17], but to date, an effective medication targeting cannabis dependence in adults has not been established [12, 14, 18, 19], leaving clinicians and patients with limited options.…”
Section: 0 Introductionmentioning
confidence: 99%